2021
DOI: 10.3390/microorganisms9061139
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum MG4296 and Lacticaseibacillus paracasei MG5012 Ameliorates Insulin Resistance in Palmitic Acid-Induced HepG2 Cells and High Fat Diet-Induced Mice

Abstract: The purpose of this study was to evaluate the capacity of Lactiplantibacillus plantarum MG4296 (MG4296) and Lacticaseibacillus paracasei MG5012 (MG5012) on insulin resistance (IR) and diabetes-related metabolic changes in palmitic acid (PA)-induced HepG2 cells and high-fat diet-induced mice. In vitro, cell-free extracts of MG4296 and MG5012 alleviated IR by increasing glucose uptake and glycogen content in PA-induced insulin-resistant HepG2 cells. In vivo, MG4296 and MG5012 supplementation markedly decreased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Among them, the basal diet contains 14% of energy from fat, 21% of energy from protein, and 64% of energy from carbohydrates. The high-fat diet contains 60% of energy from fat, 20% of energy from protein, and 20% of energy from carbohydrates ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, the basal diet contains 14% of energy from fat, 21% of energy from protein, and 64% of energy from carbohydrates. The high-fat diet contains 60% of energy from fat, 20% of energy from protein, and 20% of energy from carbohydrates ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the administration of probiotics regulates intestinal flora, suppresses inflammatory responses, improves intestinal barrier function, antagonizes each other with pathogens and produces beneficial microbial metabolites, including SCFAs and BAs ( 198 ). Studies on the molecular mechanisms of probiotic intervention in T2DM have shown that probiotics have ameliorative effects on IR and hyperglycemia ( 199 ).…”
Section: Therapeutic Options For Targeting the Gut Microbiota In T2dm...mentioning
confidence: 99%
“…All strains were deposited in the Korean Collection for Type Cultures (KCTC, Daejeon, Korea). Each strain was activated by culture in de Man, Rogosa, and Sharpe (MRS) broth (Difco, Detroit, MI, USA) for 18 h at 37 • C [20]. The dried bacterial powder used for in vivo testing was supplied by Mediogen Co., Ltd.…”
Section: Preparation Of Lactobacilli Strains and Gvmentioning
confidence: 99%